Mechanisms of Lateral Spreading in a Near-Field Buoyant River Plume Entering a Fjord - Rebecca A. McPherson; Craig L. Stevens; Joanne M. O'Callaghan; Andrew J. Lucas; Jonathan D. Nash (Frontiers in Marine Science, 2021)
Observations collected from a fast-flowing buoyant river plume entering the head of Doubtful Sound, New Zealand, were analysed to examine the drivers of plume lateral spreading. The near-field plume is characterised by flow speeds of over 2 ms −1 , and strong stratification ( N 2 > 0.1 s −2 ), resulting in enhanced shear which supports the elevated turbulence dissipation rates (ϵ > 10 −3 W kg −1 ). Estimates of plume lateral spreading rates were derived from the trajectories of Lagrangian GPS surface drifters and from cross-plume hydrographic transects. Lateral spreading rates derived from the latter compared favourably with estimates derived from a control volume technique in a previous study. The lateral spreading of the plume was driven by a baroclinic pressure gradient toward the base of the plume. However, spreading rates were underestimated by the surface drifters. A convergence of near-surface flow from the barotropic pressure gradient concentrated the drifters within the plume core. The combination of enhanced internal turbulence stress and mixing at the base of the surface layer, and the presence of steep fjord sidewalls likely reduced the rate of lateral spreading relative to the theoretical spreading rate. The estimates of plume width from the observations provided evidence of scale-dependent dispersion which followed a 4/3 power law. Two theoretical models of dispersion, turbulence and shear flow dispersion, were examined to assess which was capable of representing the observed spreading. An analytical horizontal shear-flow dispersion model generated estimates of lateral dispersion that were consistent with the observed 4/3 law of dispersion. Therefore, horizontal shear dispersion appeared to be the dominant mechanism of dispersion, thus spreading, in the surface plume layer.